Odpowiedź :
a) -(x-2)²+3(x-7)=2-(x+1)(x-1)
-x²-4x+4+3x-21=2-x²-1
-x=18 |: (-1)
x=-18
b)2x(x-1)+4=2(x-1)²
2x²-2x+4=2(x²-2x+1)
2x²-2x+4=2x²-4x+2
2x=-2 |:2
x=-1
-x²-4x+4+3x-21=2-x²-1
-x=18 |: (-1)
x=-18
b)2x(x-1)+4=2(x-1)²
2x²-2x+4=2(x²-2x+1)
2x²-2x+4=2x²-4x+2
2x=-2 |:2
x=-1
a) -(x-2)²+3(x-7)=2-(x+1)(x-1)
-( x²- 4x+4) + 3x-21= 2- (x²-1)
-x²-4x+4+3x-21= 2-x²+2
-x-17=4
-x=21/*(-1)
x=-21
b)2x(x-1)+4=2(x-1)²
2x²-2x+4=2(x²-2x+1)
2x²-2x+4=2x²-4x+2
-2x+4=-4x+2
2x=-2/:2
x=-1
-( x²- 4x+4) + 3x-21= 2- (x²-1)
-x²-4x+4+3x-21= 2-x²+2
-x-17=4
-x=21/*(-1)
x=-21
b)2x(x-1)+4=2(x-1)²
2x²-2x+4=2(x²-2x+1)
2x²-2x+4=2x²-4x+2
-2x+4=-4x+2
2x=-2/:2
x=-1